2,000 GUITARS : THE ULTIMATE COLLECTION - Bacon, Tony; Burrluck, Dave; Carter, Walter; Day, Paul; Elder, Ben; Cerken, Teja; Hunter, Dave; Jansson, Mikael; Johnston, Richard; Morrish, John; Simmons, Michael; Uwins, Jerry; et al. (New York : Chartwell Books, 2015)
The incredible array of featured instruments is arranged alphabetically by maker/manufacturer for easy access. For convenient browsing, sections are further organized by subdivisions, including solid-bodied guitars, semi-solid-bodied guitars, acoustic guitars, and bass guitars. Clean, modern spreads showcase thousands of full-color photographs of the world's most coveted guitars.
Keywords: Guitar -- Pictorial works; Illlustrated works